AHP-based prioritising of cost challenges of supply chain due to COVID-19. (20th July 2022) - Mishra, Om Prakash; Mishra, Prashant
The outbreak of COVID-19 made the world act differently in business. Preventive steps taken by governments to shut down the road, rail, air and water transportation disrupted supply chains of most of the businesses. Whereas supply chains of essentials like food and pharmaceutical kept working in stressed environment. This paper is highlighting the cost of supply chain due to the outbreak of COVID-19 as a pandemic. The main stakeholders of a supply chain such as supplier, manufacturer, distributor, retailer and customer were tweaked to protect people from infection. New norms such as sanitisation, social distancing, use of personal protective gears increased the lead time and escalated the cost of supply chain management significantly. AHP has been used to model the cost of supply chain management citing a case study of three key industries. It has been seen that the restricted human movement remained pivotal in sky rocketing cost of supply chain.